VARIATION IN TREE AND EPIPHYTE RICHNESS IN AN URBAN AREA OF THE ATLANTIC FOREST BIOME - Maler de Oliveira, Luan; da Silva Rasvailer, Vinícius; Zampar, Rafael; Benedito, Evanilde (Acta Biologica Brasiliensia, 2025)
This study investigates the density and species richness of arboreal and epiphytic communities in a central urban area of Campo Mourão, Paraná, comparing samples from 2017 and 2025. Although the total number of trees remained relatively stable (with a slight decrease from 78 to 70 individuals), significant changes in species composition were observed. Notably, there was a 78.5% increase in the abundance of Moquilea tomentosa, accompanied by declines of 55.5% in Ligustrum lucidum and 44.4% in Cenostigma pluviosum. These shifts in the arboreal community influenced the associated epiphytic assemblage, which experienced a 49.6% reduction in recorded individuals (from 155 to 78) and the loss of certain species on specific phorophytes. Although overall diversity (Shannon-Wiener index) and dominance (Simpson index) showed no significant changes, spatial patterns varied considerably: areas with a higher dominance of M. tomentosa, zones affected by tree removal exhibited reduced diversity, and sectors with limited vegetation renewal maintained high dominance levels. These findings highlight that inadequate urban tree management can compromise epiphyte diversity and persistence, underscoring the need to conserve native, large phorophytes to support urban biodiversity.